Pengaruh Lingkungan, Budaya, Dan Pengalaman Kerja Terhadap Produktivitas Kerja Karyawan Di PT Tiga Serangkai - Ayu Rizka Lesmana; Ida Ayu Kade Rachmawati Kusasih (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to determine and test what factors can affect work productivity, namely: (1) work environment, (2) organizational culture, (3) work experience. This research uses quantitative categories. The source of data processed in the form of the results of distributing questionnaires.The population of this study were all production employees of PT Tiga Serangkai. The number of samples obtained by the Slovin method amounted to 55 respondents. Simple Random Sampling technique was used in sampling in this study. This study uses multiple regression for data analysis. The data analysis techniques used are validity and reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, hypothesis tests consisting of F tests and t tests, and coefficient of determination tests. The results of this study are (1) the work environment has a significant effect on work productivity, (2) organizational culture has a significant effect on work productivity, (3) work experience has no effect on work productivity.